Алгебри квазіарних та бі-квазіарних реляцій - Нікітченко, М.С.; Шкільняк, С.С. (Проблеми програмування, 2016)
Запропоновано поняття квазіарної реляції (відношення), введено операції над такими реляціями, описано алгебри квазіарних реляцій. Доведено ізоморфізм алгебри квазіарних реляцій та першопорядкової алгебри тотальних однозначних квазіарних предикатів. Побудовано алгебри бі-квазіарних реляцій, задані на множинах пар квазіарних реляцій. Визначено різні підкласи таких алгебр та досліджено їх зв’язки з алгебрами часткових однозначних, тотальних неоднозначних, часткових неоднозначних, монотонних, антитонних квазіарних предикатів. Предложено понятие квазиарной реляции (отношения), введены операции над такими реляциями, описаны алгебры квазиарных реляций. Доказан изоморфизм алгебры квазиарных реляций и первопорядковой алгебры тотальных однозначных квазиарных предикатов. Построены алгебры биквазиарных реляций, заданные на множествах пар квазиарных реляций. Определены различные подклассы таких алгебр, иссследованы их связи с алгебрами частичных однозначных, тотальных неоднозначных, частичных неоднозначных, монотонных, антитонных квазиарных предикатов. The notion of quasiary relation which can be considered generalization of the notion of traditional n-ary relation is proposed. A number of algebras of quasiary relations is built and investigated. Alongside with conventional operations of union, intersection, and complement, special nominative operations of renomination and quantification are defined for quasiary relations. The isomorphism between the algebra of quasiary relations and the first-order algebra of total single-valued quasiary predicates is proved. Algebras of bi-quasiary relations defined over sets of pairs of quasiary relations are built. The isomorphism between algebras of bi-quasiary relations and algebras of quasiary predicates is proved. The following subclasses of algebras of bi-quasiary relations are specified: algebras of partial single-valued (functional), total, total many-valued bi-quasiary relations. For all defined subclasses their counterparts of the classes of algebras of quasiary predicates are described. Also subalgebras of the algebra of bi-quasiary relations induced by upward closedness and downward closedness are investigated.